Self-Readiness of Islamic Religious Education Students to Enter the Business World and Employment in Manado - Mustafa Mustafa (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to identify Islamic religious education students' self-readiness to enter the world of business and employment. A survey study was deployed as the design of the research. The population is 60 students and the sample taken is only 27 final semester students who have carried out the Integrated Teaching Professional Practice (Praktek Profesi Keguruan Terpadu/ PPKT) at schools/madrasas which was carried out for 3 months from September 2021 to November 2021. The data of this research was obtained from data respondents directly through a questionnaire to measure the students’ knowledge, skills, and affective factors in preparing themselves to enter the world of business and employment. From the results of this study, it was revealed that knowledge was in the 79 percent category, skills were in the 88 percent category, and attitudes were in the 79 percent category. Thus, the results of the overall analysis for service and managerial productive work are in the 85 percent category. This finding indicates that Islamic religious education students are dominantly ready to contribute to the professional world as employees.